Adopting metaverse‐related mixed reality technologies to tackle urban development challenges: An empirical study of an Australian municipal government. Issue 1 (14th February 2023) - An, Aaron
Abstract: Fast‐growing urban areas bring challenges to government authorities. The urban planning system in Australia is still very analogue with paper‐based systems as standard practice. Two‐dimensional document‐based blueprints and Geographic Information System (GIS) maps do not always give stakeholders and investors the necessary insights. By exploring Mixed Reality (MR) application at the municipal government level, this research explains how metaverse‐related immersive technologies can assist the government in better engaging with stakeholders and potential partners to improve their understanding of the urban environment and showcase future city developments to foster new opportunities and contribute to the development of the real living world. Abstract : A study of a Mixed Reality (MR) application at the municipal government level, explains how immersive technologies help the government to better engage with stakeholders and potential partners and showcase future city developments to foster new opportunities and contribute to the development of a fast‐growing city.